Gut microbiota in COVID-19: new insights from inside. (31st December 2023) - Zhou, Bingqian; Pang, Xiaoqi; Wu, Jingyi; Liu, Tianyu; Wang, Bangmao; Cao, Hailong
ABSTRACT: The epidemic of coronavirus disease-19 (COVID-19) has grown to be a global health threat. Gastrointestinal symptoms are thought to be common clinical manifestations apart from a series of originally found respiratory symptoms. The human gut harbors trillions of microorganisms that are indispensable for complex physiological processes and homeostasis. Growing evidence demonstrate that gut microbiota alteration is associated with COVID-19 progress and severity, and post-COVID-19 syndrome, characterized by decrease of anti-inflammatory bacteria like Bifidobacterium and Faecalibacterium and enrichment of inflammation-associated microbiota including Streptococcus and Actinomyces . Therapeutic strategies such as diet, probiotics/prebiotics, herb, and fecal microbiota transplantation have shown positive effects on relieving clinical symptoms. In this article, we provide and summarize the recent evidence about the gut microbiota and their metabolites alterations during and after COVID-19 infection and focus on potential therapeutic strategies targeting gut microbiota. Understanding the connections between intestinal microbiota and COVID-19 would provide new insights into COVID-19 management in the future.